Connecting Knowledge of Rule-breaking and Perceived Red Tape: How Behavioral Attribution Influences Red Tape Perceptions. Issue 1 (1st August 2016) - Davis, Randall S.; Pink-Harper, Stephanie A.
ABSTRACT: Since the 1990s, governmental strategies for enhancing organizational performance have sought to reduce the amount of red tape public employees face. These strategies assume that employees' perceptions of rules as red tape stem solely from the actual content of rules, but a sizable body of public management research has revealed the psychological processes through which red tape perceptions develop. This article builds on psychological process models of perceived red tape by applying attribution theory to explore how an organization's social context influences red tape perceptions. Findings illustrate that individuals will judge a rule to be red tape based on information conveyed second-hand regarding the rule-breaking behavior of others.